1994
DOI: 10.1016/s0741-5214(94)70109-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased limb salvage by the use of unconventional foot amputations

Abstract: Limb salvage in the presence of ischemic foot necrosis requires revascularization followed by debridement or partial foot amputation. Necrosis extending beyond the toes and metatarsal heads may require the use of unconventional types of amputations. Methods: Over a 15-year period 2105 ischemic limbs were treated with infrainguinal revascularization. In 98 cases, extensive foot necrosis was then managed with amputations, including 59 modified Chopart, 14 Lisfranc, 17 Pirogoff and 8 Syme amputations. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 6 publications
3
44
0
2
Order By: Relevance
“…" information for inclusion even after contacting the authors for missing information. 6,[40][41][42] Three of the 4 references did not clearly state if the patients who underwent a Chopart amputation had a diagnosis of diabetes. 6,40,41 Two of the 4 references did not state the postoperative follow-up time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…" information for inclusion even after contacting the authors for missing information. 6,[40][41][42] Three of the 4 references did not clearly state if the patients who underwent a Chopart amputation had a diagnosis of diabetes. 6,40,41 Two of the 4 references did not state the postoperative follow-up time.…”
Section: Resultsmentioning
confidence: 99%
“…6,[40][41][42] Three of the 4 references did not clearly state if the patients who underwent a Chopart amputation had a diagnosis of diabetes. 6,40,41 Two of the 4 references did not state the postoperative follow-up time. 40,41 One of the references also did not report if the patients returned to ambulation postoperatively in a prosthetic device or if any complications occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shortening makes barefoot walking difficult. Burgess (1966) and Chang et al (1994) also suggested an achilles tenotomy to improve balance. Our alternative method, consisting of fusion of the talus both to the tibia and the calcaneus with a simultaneous correction of the equinus and varus contracture, preserves leg length for better barefoot walking and creates stability of shape inside a prosthetic socket.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of Pirogoff's amputation is its excellent weightbearing without prosthesis, and recent data (Nakhgevany and Rhoads, 1984;Ham et al, 1992;Rijken and Raaymakers, 1995) indicate good long term outcomes. Pirogoff himself described the surgical procedure thus: "the tuberosity of the calcaneus remaining in the posterior flap can extend to the end of the bones of the leg, and by doing this, the leg is lengthened by at least 1 1 ⁄3 inches and it can serve as the most important point of weight bearing since it is almost on the same plane with the sole of the healthy foot" (Chang et al, 1994).…”
Section: Specific Anatomico-surgical Achievementsmentioning
confidence: 99%